2019
DOI: 10.1029/2018jd028859
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Global Downscaled Versus Bottom‐Up Fossil Fuel CO2 Emissions at the Urban Scale in Four U.S. Urban Areas

Abstract: Spatiotemporally resolved urban fossil fuel CO2 (FFCO2) emissions are critical to urban carbon cycle research and urban climate policy. Two general scientific approaches have been taken to estimate spatiotemporally explicit urban FFCO2 fluxes, referred to here as “downscaling” and “bottom‐up.” Bottom‐up approaches can specifically characterize the CO2‐emitting infrastructure in cities but are labor‐intensive to build and currently available in few U.S. cities. Downscaling approaches, often available globally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 85 publications
(118 reference statements)
0
78
0
Order By: Relevance
“…Assessment of prior emissions errors in gridded field is difficult (Andres et al, 2016), which is usually done by comparing emission inventories at an aggregated spatial resolution (Hutchins et al, 2017; Oda et al, 2015). The ODIAC data have been compared to the Hestia emission product (Gurney et al, 2019), which is one of the most accurate and complete emission inventories at the scale of buildings and street segments as evaluated against in situ tower measurements (Lauvaux et al, 2016). At 1‐km × 1‐km spatial scale, the result reveals a low‐emission limit in ODIAC driven by saturation of the nighttime light spatial proxy, and the median difference ranging between 47% and 84%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of prior emissions errors in gridded field is difficult (Andres et al, 2016), which is usually done by comparing emission inventories at an aggregated spatial resolution (Hutchins et al, 2017; Oda et al, 2015). The ODIAC data have been compared to the Hestia emission product (Gurney et al, 2019), which is one of the most accurate and complete emission inventories at the scale of buildings and street segments as evaluated against in situ tower measurements (Lauvaux et al, 2016). At 1‐km × 1‐km spatial scale, the result reveals a low‐emission limit in ODIAC driven by saturation of the nighttime light spatial proxy, and the median difference ranging between 47% and 84%.…”
Section: Discussionmentioning
confidence: 99%
“…The prior emission uncertainty σ a is set up based on reported estimations in literature, as the ODIAC data product did not provide uncertainty estimates. At annual scales, Gurney et al (2019) investigated the difference between the ODIAC data and a high‐resolution bottom‐up estimate product (Hestia) in four U.S. urban areas, showing the differences of whole‐city emissions ranging from −1.5% to +20.8%. Oda et al (2019) found differences of about 40% by comparing a satellite‐derived annual emissions product to a gridded national inventory at 25‐km resolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These transport and dispersion models are used to interpret observations from both aircraft and tower stations and in atmospheric inverse analyses to estimate fluxes of CO2 and CH4 from the cities of Washington, D.C. and Baltimore, Maryland (Lopez-Coto et al, in prep; Ghosh et al, in prep.). A high-resolution fossil-fuel CO2 inventory, Hestia, 70 is also being developed for this project (Gurney et al, 2012;Gurney et al, 2019).…”
Section: Introduction 20mentioning
confidence: 99%
“…1.1 CO 2 concentration field from the Hestia datasetTo compute a high-resolution three-dimensional field of CO 2 concentrations to be used as input for the radiative transfer simulations, annual estimates of fossil fuel CO 2 emissions for the city of Indianapolis in the year 2015 are used. These data are generated by the Hestia Project(Gurney et al, 2012(Gurney et al, , 2019 where the fossil fuel CO 2 emissions are quantified in urban areas down to the scale of individual buildings and streets using a bottom-up approach. The results for the city of Indianapolis are25 gridded and archived at a spatial resolution of 200 × 200 m 2 .…”
mentioning
confidence: 99%